The understanding of the zakat an income among the staff in UiTM Selangor, Puncak Alam Campus / Anis Raihana Mohd Zaini. - Mohd Zaini, Anis Raihana (2020)
Zakat is one of the pillars of Islam that must be performed on all Muslims in this world. When it comes to zakat obligations, people only know certain types of zakat that are obligated to be issued. There are two type of zakat; zakat fitrah and zakat property. Because of that, Zakat an Income became a duty and obligation to Muslim to pay it. Zakat on income also is one of the emerging issues among Syariah scholar where they might have various opinions regarding it. Therefore, this paper aims to study about the understanding of the Zakat an Income among the staff in UiTM Selangor, Puncak Alam Campus.The study utilizes a quantitative research design by using survey and questionnaire with the selected respondent which is staff in UiTM Puncak Alam. The finding of this study indicated that majority of the staff of UiTM Puncak Alam known about Income zakat and almost half of them had also implemented by paying income zakat in their life. Then, there is a great opportunity for improvement in the future with regard to understanding about income zakat.